The effect of high level tennis matches on urine steroid profiles in professional tennis players - Muñoz, D.; Toribio, F.; Timon R.; Olcina, G.; Maynar, J. I.; Maynar, M. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Modern day, tennis matches are characterized by shorter and more intense efforts with players enduring great physical and psychological stress. The aim of this study was to evaluate acute changes in the urinary steroid profile of elite tennis players following professional tournament matches. METHODS: Eight professional male tennis players participated in this study. Urine samples were collected before and after tennis matches corresponding to the quarter finals of the Spanish Tennis Masters. RESULTS: After the match, there was a significant fall (P<0.05) in testosterone, androsterone, etiocholanolone, and dehydroepiandrosterone (DHEA). Cortisone increased whereas tetrahydrocortisone (THE) decreased. The anabolic/catabolic hormone ratio also decreased, although only the fall in total suprarenal androgen (TSA)/total corticosteroid (TC) and DHEA/(THE+THF) ratios had a significant decrease (P<0.05). CONCLUSION: These results indicate that a professional tennis match modifies the urine steroid profiles of players, increasing corticosteroid and decreasing androgen excretion in urine, suggesting an important adrenal activation.